2013
DOI: 10.5350/dajpn2013260403
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of suicide attempt and suicidal ideation with insight, depression and severity of illness in schizophrenic patients

Abstract: ÖZETŞizofreni hastalarında özkıyım girişimi ve özkıyım düşüncesinin, hastalık şiddeti, depresyon ve içgörü ile ilişkisi Amaç: Bu çalışmada şizofreni hastalarında özkıyım girişimi ve özkıyım düşüncesinin hastalık şiddeti, depresyon ve içgörü ile ilişkisi araştırılarak, şizofreni hastalarında özkıyım riskini yordayabilecek ölçütlerin gelişmesine katkı sağlanması amaçlanmıştır. Yöntem: Bakırköy Prof. Dr. Mazhar Osman Ruh Sağlığı ve Sinir Hastalıkları Eğitim ve Araştırma Hastanesi psikiyatri servislerinde DSM-IV-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
1
6
1
Order By: Relevance
“…Unlike in previous studies (e.g., Tarrier et al, 2004; Umut et al, 2013; Yan et al, 2013), we did not find a significant relationship between negative symptoms and suicide ideation; however, we identified a significant interaction. Therefore, our findings fill a gap in the existing literature related to the interactive effects of negative symptoms, which may influence social functioning (e.g., Kring et al, 2013), and social role functioning in relation to suicide risk.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unlike in previous studies (e.g., Tarrier et al, 2004; Umut et al, 2013; Yan et al, 2013), we did not find a significant relationship between negative symptoms and suicide ideation; however, we identified a significant interaction. Therefore, our findings fill a gap in the existing literature related to the interactive effects of negative symptoms, which may influence social functioning (e.g., Kring et al, 2013), and social role functioning in relation to suicide risk.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, individuals with prominent negative symptoms may not experience a thwarted need for belonging and, as such, may not be at elevated risk for suicide due to thwarted belongingness. Instead, suicide risk among individuals with elevated negative symptoms (e.g., Umut et al, 2013; Yan et al, 2013) may be due to other causes, such as demoralization (Drake et al, 1985). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, reviews have found inverse relationships between negative symptoms and suicide risk (Hor and Taylor, 2010) or no relationships between these variables (Hawton et al, 2005). Studies have also observed a positive relationship between suicide risk and negative symptoms (Tarrier et al, 2004; Umut et al, 2013; Yan et al, 2013). The inconsistent findings do not appear to be dependent on the suicide-related outcome of interest (e.g., ideation, attempts, death).…”
Section: Introductionmentioning
confidence: 97%
“…Jovanovic et al (2013) found that anxiety was associated increased suicide risk, defined as previous suicide attempts and/or current suicide ideation. Depressive symptoms have also been associated with suicide risk (Jovanovic et al, 2013), as well as previous suicide attempts (Umut et al, 2013) and suicide ideation (Umut et al, 2013; Yan et al, 2013) separately. Therefore, it is important to account for psychiatric symptoms such as depression and anxiety when examining predictors of suicide risk in individuals with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%